Associations between acute exposures to PM2.5 and carbon dioxide indoors and cognitive function in office workers: a multicountry longitudinal prospective observational study. (9th September 2021) - Cedeño Laurent, Jose Guillermo; MacNaughton, Piers; Jones, Emily; Young, Anna S; Bliss, Maya; Flanigan, Skye; Vallarino, Jose; Chen, Ling Jyh; Cao, Xiaodong; Allen, Joseph G
Abstract: Despite evidence of the air pollution effects on cognitive function, little is known about the acute impact of indoor air pollution on cognitive function among the working-age population. We aimed to understand whether cognitive function was associated with real-time indoor concentrations of particulate matter (PM2.5 ) and carbon dioxide (CO2 ). We conducted a prospective observational longitudinal study among 302 office workers in urban commercial buildings located in six countries (China, India, Mexico, Thailand, the United States of America, and the United Kingdom). For 12 months, assessed cognitive function using the Stroop color-word test and addition–subtraction test (ADD) via a mobile research app. We found that higher PM2.5 and lower ventilation rates, as assessed by CO2 concentration, were associated with slower response times and reduced accuracy (fewer correct responses per minute) on the Stroop and ADD for eight out ten test metrics. Each interquartile (IQR) increase in PM2.5 (IQR = 8.8 μ g m −3 ) was associated with a 0.82% (95% CI: 0.42, 1.21) increase in Stroop response time, a 6.18% (95% CI: 2.08, 10.3) increase in Stroop interference time, a 0.7% (95% CI: −1.38, −0.01) decrease in Stroop throughput, and a 1.51% (95% CI: −2.65, −0.37) decrease in ADD throughput. For CO2, an IQR increase (IQR = 315 ppm) was associated with a 0.85% (95% CI: 0.32, 1.39) increase in Stroop response time, a 7.88% (95% CI: 2.08, 13.86) increase in Stroop interference time, a 1.32% (95% CI: −2.3, −0.38) decrease in Stroop throughput, and a 1.13% (95% CI: 0.18, 2.11) increase in ADD response time. A sensitivity analysis showed significant association between PM2.5 in four out of five cognitive test performance metrics only at levels above 12 μ g m −3 . Enhanced filtration and higher ventilation rates that exceed current minimum targets are essential public health strategies that may improve employee productivity.